Resilience of educational infrastructure in Nepal: A mixed methods approach to structural and functional assessment - Kishor Badu; Khem Raj Joshi; Dipesh Dhami; Dipak Raj Bhatt; Shriya Bohara; Bhim Kunwar; Birendra Kumar Bohara (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2025)
Higher education institutions in developing nations are growing swiftly to address the increasing demand for quality education; however, their physical infrastructures frequently lack adequate evaluation regarding safety, functionality, and environmental performance. This study focuses on the Education and Humanities Building at Far Western University (FWU) in Nepal, two main academic structures built in the early 2010s that have been in continuous use without maintenance. A mixed-methods strategy was utilized, including visual assessments, non-destructive testing (NDT) using a rebound hammer, physical measurements, user surveys, and a review of secondary data. The results indicate moderate material strengths (14.46 MPa for masonry walls, 17.0 MPa for masonry columns, and 17.4–26.63 MPa for slabs), which are typical of older institutional buildings, but there are significant issues such as cracks, moisture infiltration, corrosion, and the lack of expansion joints. Assessments of indoor environmental quality revealed high thermal discomfort, as the temperatures of second-floor slabs exceeded 50 °C, inadequate ventilation due to low window-to-wall ratios (<20%), and insufficient daylighting. User surveys (n=50) revealed ongoing issues concerning structural cracks, congested circulation areas, leaking roofs, and poor maintenance, all of which adversely impact safety and learning environments. The results emphasize the critical necessity for preventive maintenance, structural upgrades, and functional enhancements to comply with Nepal National Building Code (NBC) standards and international guidelines for healthy educational settings. By merging technical evaluations with user feedback, this research offers evidence-based suggestions for improving the resilience, safety, and sustainability of higher education infrastructure in regions of far western Nepal that are prone to seismic activity.